SIFAT ORGANOLEPTIK DAN KANDUNGAN TOTAL FENOL MINUMAN REMPAH TRADISONAL (MINUMAN SECANG) - Dwi Eva Nirmagustina; Zulfahmi Zulfahmi; Oktafrina Oktafrina (Jurnal Teknologi & Industri Hasil Pertanian, 2011)
Secang drink is an Indonesian traditional drink, especially from Yogyakarta and Central Jawa, that is made from secang wood (Caesalpinia sappan L) which gives red color like wine.  Except secang wood in secang drink, there are also other spices, such as ginger, clove, lemongras, cinnamon bark, cardamon, and nutmeg.  The active component of spices mostly from phenolic compound, including brazilin dan brazilein (secang wood), zingiberen, gingerol, dan shogaol (ginger), eugenol (clove), geraniol, citronellal, citronellol, lemonene (lemongrass), sineol dan sinamaldehida (cinnamon bark), cineol dan pinen (kapulaga), myristicin dan safrol (nutmeg).  This research objectives were to investigate the effect of various types of phenols in the spices of the organoleptic properties and phenol total content of secang drink. The treatments were the formulation of secang drink, secang wood (F1), secang wood and red ginger (F2), secang wood, red ginger, lemongrass (F3), secang wood, red ginger, lemongrass, clove (F4), secang wood, red ginger, lemongress, clove, cinnamon bark (F5), secang wood, red ginger, lemongrass, clove, cinnamon bark, cardamon (F6), secang wood, red ginger, lemongrass, clove, cinnamon bark, cardamon, nutmeg (F7).  The formulation of secang drink were 1 liter water, 5 stalk secang wood (1 cm), 100 gram red ginger, 2 clove, 2 lemongrass, 2 stalk cinnamon bark (1 cm), 2 cardamon, 1/3 nutmeg, 100 gram sugar, 1 tablespoon.  Based on the average value of the panelist's favorite degree on color, aroma, flavor, and overall appearance of the most high secang drinks in a row is the formulation 1 (3,4), formulation 2 (3.0), formulation 2 (2.8 ), and the formulation of 2, 4, 5, and 6 (2.8). There were differences between the treatment of color and aroma, but nots between the treatment of taste and overall appearance.  The formulation 1 of secang drinks contained the lowest total phenol (117.989 mg/L) and the  formulation 7 of secang drinks contained the highest total phenol (186.055 mg/L). There was not any difference between the treatment of total phenol content of secang drinks.